2019
DOI: 10.2478/ats-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of leadership training needs of executive members of farmer-groups in Oyo State, Nigeria

Abstract: The failure of farmers’ associations in Nigeria has been linked to leadership incompetency. In this study we investigated the leadership training needs of executives of farmers’ associations in Oyo State. Specifically, we examined the importance associated with the leadership roles by the executives, investigated their competence levels and identified the constraints they face in carrying out their roles. A two-stage sampling procedure was used to select 195 respondents on which an interview schedule was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Van Velsor et al (1998) as cited by Sessoms (2004) defined leadership development as "The expansion of a person's capacity to be effective in leadership roles and processes" (p. 1). Omotesho et al (2019) affirmed that the need for leadership development has been presented in many studies, although specific areas of need remain unclear. Through their study, three most critical areas of leadership development need were identified including group resources mobilization, monitoring and control.…”
Section: Leadership Development Needs and Methodsmentioning
confidence: 99%
“…Van Velsor et al (1998) as cited by Sessoms (2004) defined leadership development as "The expansion of a person's capacity to be effective in leadership roles and processes" (p. 1). Omotesho et al (2019) affirmed that the need for leadership development has been presented in many studies, although specific areas of need remain unclear. Through their study, three most critical areas of leadership development need were identified including group resources mobilization, monitoring and control.…”
Section: Leadership Development Needs and Methodsmentioning
confidence: 99%